2013
DOI: 10.1038/ijo.2013.78
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between dairy consumption and changes of body weight and waist circumference: the Framingham Heart Study

Abstract: Background Dairy foods are nutrient-dense and may be protective against long-term weight gain. Objective We aimed to examine the longitudinal association between dairy consumption and annualized changes in weight and waist circumference (WC) in adults. Methods Members of the Framingham Heart Study Offspring Cohort who participated in the 5th through 8th study examinations (1991–2008) were included in these analyses (3,440 participants with 11,683 observations). At each exam, dietary intake was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
81
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 49 publications
7
81
1
1
Order By: Relevance
“…The main food sources contributing to the nutrient intakes of PC4-dairy (particularly milk), read meat and poultry, and fish and shellfish (Online Resource 2)-have been investigated individually in a number of cohort studies and randomized controlled trials (RCT), but with no clear conclusion with regard to weight change [24][25][26][27], with the exception of red or processed meat intake, which promote unhealthy weight gain and obesity [19,28]. However, it is very likely that the combined intake of multiple dietary factors act synergistically [6].…”
Section: Discussionmentioning
confidence: 99%
“…The main food sources contributing to the nutrient intakes of PC4-dairy (particularly milk), read meat and poultry, and fish and shellfish (Online Resource 2)-have been investigated individually in a number of cohort studies and randomized controlled trials (RCT), but with no clear conclusion with regard to weight change [24][25][26][27], with the exception of red or processed meat intake, which promote unhealthy weight gain and obesity [19,28]. However, it is very likely that the combined intake of multiple dietary factors act synergistically [6].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fermented dairy products and probiotic bacteria may have beneficial health effects on blood cholesterol, blood pressure, and immune function (46,47) and may provide prophylactic protection against heart disease (48), diabetes (49,50), and stroke (51). Moreover, in prospective cohort studies, increased consumption of yogurt and other dairy foods was associated with less weight gain and lower waist circumference (52,53). However, in the present study, higher dairy product consumption was associated with higher BMI (Table 1), and an interaction with BMI was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Both yogurt and fruit have been identified as protective against weight gain (75). Results from examinations 5-8 of the Framingham Heart Study Offspring Cohort (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) found that participants who consumed yogurt regularly (i.e., $3 times/wk) had a smaller annual weight gain and waist circumference increase than those consuming <1 serving/wk (78). A review on yogurt and weight management examined 5 observational studies and found inconsistent results between studies with regards to yogurt's association with BMI, waist circumference, and sex (79).…”
Section: Epidemiologic Studies: Fruit Yogurt and Cardiometabolic Hementioning
confidence: 99%
“…The influence of yogurt against weight gain may be attributed to the changes in colonic bacteria from the ingestion of abundant yogurt probiotics (75), whey, casein, and bioactive peptides (78). Yogurt consumption may enhance the proportion of beneficial gut microbiota that are thought to be involved in weight maintenance via regulation of energy uptake and extraction (82).…”
Section: Epidemiologic Studies: Fruit Yogurt and Cardiometabolic Hementioning
confidence: 99%